2012
DOI: 10.1074/jbc.m111.306563
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of High Affinity Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP)-Binding Proteins in Sea Urchin Egg

Abstract: Background: Nicotinic acid adenine dinucleotide phosphate (NAADP) regulates calcium release from internal acidic stores via two-pore channels (TPCs).Results: A novel photosensitive probe (5-azido-NAADP) identified high affinity NAADP binding sites that interact with, but are distinct from, TPCs.Conclusion: High affinity NAADP-binding proteins complex with TPCs.Significance: This work provides new mechanistic insights into how NAADP regulates calcium release via TPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 31 publications
(60 reference statements)
5
130
0
Order By: Relevance
“…Third, whereas the intracellular target of InsP3 has long been recognized, the selective receptor of the two newly discovered second messengers, cADPr and NAADP, has recently been questioned. Indeed, a couple of recent investigations demonstrated that the genetic suppression of TPC1-2 does not prevent cell labeling by NAADP [415,416] . Conversely, the same studies suggested that a 22-and 23-kDa pair of accessory proteins might serve as NAADP receptors and regulate the activity of its target channels, including TPC1-2 in ECs and RyRs in the immune system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, whereas the intracellular target of InsP3 has long been recognized, the selective receptor of the two newly discovered second messengers, cADPr and NAADP, has recently been questioned. Indeed, a couple of recent investigations demonstrated that the genetic suppression of TPC1-2 does not prevent cell labeling by NAADP [415,416] . Conversely, the same studies suggested that a 22-and 23-kDa pair of accessory proteins might serve as NAADP receptors and regulate the activity of its target channels, including TPC1-2 in ECs and RyRs in the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…TRPC3-and TRPC6-induced Ca 2+ inflow underpin the stimulatory effect of VEGF on endothelial proliferation, migration and permeability [18,231,236] , while ATP exploits TRPC3 to activate NF-κB and increase vascular cell adhesion molecule-1 expression [237] . TRPC3-driven NO synthesis and vasore- TRPV1 TRPV2 TRPV3 TRPV4 TRPV5 TRPV6 PCa/PNa and conductance (pS) [202] 10, 35-80 1-3, NM 12, 172 6, 90 > 100, 75 > 100, 40-70 Human coronary artery ECs [300] (+RT-PCR, WB, IHC) Human pulmonary artery ECs [415] +(RT-PCR) +(RT-PCR) +(RT-PCR) Human pulmonary microvascular ECs +(RT-PCR) Human cerebral microvascular ECs [272] +(RT-PCR, IC) Human cerebral arterioles ECs [305] +(RT-PCR, IHC) Human dermal microvascular ECs [319] +(RT-PCR, WB) Breast cancer derived microvascular ECs [319] +(RT-PCR, WB) Human umbilical vein ECs [227,277,296,301] +(RT-PCR) +(WB, IHC) Mouse aortic ECs [280,285,299,306] +(WB) +(RT-PCR, WB, NM, IHC) Mouse pulmonary artery ECs [313] +(WB, IHC) Mouse mesenteric artery ECs [27,280,302] +(RT-PCR, WB, IC) +(RT-PCR, IC) Mouse cerebral microvascular ECs +(RT-PCR) +(RT-PCR, WB) +(RT-PCR) Mouse dermal microvascular ECs [307] +(RT-PCR, WB) Mouse carotid artery ECs [290,296] +(IHC) Rat mesenteric artery ECs [226,275,302] +(WB) +(WB, IC, IHC) Rat femoral artery ECs [312] +(RT-PCR, IC) Rat pulmonary artery ECs [303] +(WB, IHC) Rat renal artery ECs [303] +(IHC) Rat cardiac microvascular ECs [303,…”
Section: A Drop In Luminal Camentioning
confidence: 99%
“…The apparent modification in the downstroke velocity could probably be due to the decrease of extrusion mechanisms. Finally, NAADP evoked Ca 2+ signals by activation of RyR and TPCN channels [27,67] directly or after interaction with a NAADP-binding cytosolic protein [60]. TPCN1 is required in NAADP-induced Ca 2+ signal [7] and as observed in MCA, the increase of TPCN1 is sufficient to explain the increase of NAADP-induced Ca 2+ response.…”
Section: +mentioning
confidence: 94%
“…Literature suggest proton-permeable ion channels activated by NAADP or Ca 2C ; 18 although photoaffinity labeling studies suggest that NAADP does not directly bind TPCs. 19,20 However other studies indicate Na C -selective channels regulated by phosphoinositide-3,5-bisphosphate (PI(3,5)P 2 ) and ATP. 21,22 Further studies may still be needed to account for both sets of data.…”
Section: Introductionmentioning
confidence: 99%